Implementation of Contract Hybrid Concept in Multi Services Products (Aplication of the Warranty Bank Products/Kafalah in Syariah Banks) - Muhammad Firmansyah (International Journal of Nusantara Islam, 2016)
Product of multi services in sharia banks presented in order to meet the needs of society as well as the development of the era transactions that course in accordance with Islamic principles, then the ownership  in  the syariah products  including  multi  product  in  Islamic banking  services  using  the concept of multi akad therein. This is done so that innovation in Islamic banking products had been developed so that it can be chosen by the public in conducting business transactions. Likewise, the multi-service bank guarantee products in Islamic banking, is a multi product contract, where there is more than one contract. Bank guarantees in Islamic banking is generally called kafalah product because this product is Kafalah main contract, followed by Ijarah contract, wadiah, and qardh. This paper  examines  the  concept  of  multi-contract/contract executed  hybrid  shariah  banking  at  bank product warranty/kafalah